The USE OF SHORT STORY TO IMPROVE STUDENTS' VOCABULARY MASTERY: Penggunaan Cerita Pendek Untuk Meningkatkan Penguasaan Kosa Kata Siswa - Rohmani, Ihsaniati; Muhsinin; Rahmat, Hery (Satya Widya, 2023)
This research aimed to find out whether or not the use of Short Stories can improve vocabulary mastery. The researcher used a pre-experimental one group with pretest and post-test design. The instrument used to collect data of this research is a test. The researcher used a vocabulary translating test that consisted of 10 questions and a vocabulary matching test that consisted of 10 questions. There were 20 questions for pre-test and 20 questions for post-test. The research findings show that the students' vocabulary mastery improved by using short Stories. It was shown on the mean score of pre-test 44.82 while the mean score of post-test 76.42 which means higher than pre-test The conclusion is drawn based on the results obtained from the paired-sample T-test.. The significant sig. (2-tailed) of pre-test and post-test 0.000. The sig. (2- tailed) is 0.000 < 0.05 which means the pre-test and post-test has sig < a and can be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. From these findings, there was an improvement in vocabulary mastery and it was concluded that the use of Short Stories can improve vocabulary mastery.